Metabolic Syndrome Impairs Notch Signaling and Promotes Apoptosis in Chronically Ischemic Myocardium - Elmadhun, Nassrene Y. (2014)
OBJECTIVE: Impaired angiogenesis is a known consequence of metabolic syndrome (MetS), however, the mechanism is not fully understood. Recent studies have shown that the Notch signaling pathway is an integral component of cardiac angiogenesis. We tested in a clinically relevant swine model the effects of MetS on Notch and apoptosis signaling in chronically ischemic myocardium. METHODS: Ossabaw swine were fed either a regular diet (CTL, n=8) or a high-cholesterol diet (MetS, n=8) to induce MetS. An ameroid constrictor was placed to induce chronic myocardial ischemia. Eleven weeks later, animals underwent cardiac harvest of the ischemic myocardium. RESULTS: There was down-regulation of pro-angiogenesis proteins Notch2, Notch4, Jagged2, Ang1 and ENOS in the MetS group compared to CTL. There was also up-regulation of pro-apoptosis protein Caspase8, and down-regulation of anti-angiogenesis protein pFOX03, and pro-survival proteins pP38 and HSP90 in the MetS group. Cell death was increased in the MetS group compared to CTL. Both CTL and MetS groups had similar arteriolar count and capillary density, and Notch3 and Jagged1 were both similarly concentrated in the smooth muscle wall in both groups. CONCLUSIONS: MetS in chronic myocardial ischemia significantly impairs Notch signaling by down regulating Notch receptors, ligands and pro-angiogenesis proteins. MetS also increases apoptosis signaling, decreases survival signaling and increases cell death in chronically ischemic myocardium. Although short-term angiogenesis appears unaffected in this model of early MetS, the molecular signals for angiogenesis are impaired, thus suggesting that inhibition of Notch signaling may underlie decreased angiogenesis in later stages of MetS.